Crescimento de crianças nascidas prematuras após a alta hospitalar e a autoeficácia materna - Rover, Milene de Moraes Sedrez (2024)
Objective: To analyze the relationship between maternal self-efficacy (SE), maternal clinical factors, variables related to premature infants (PT), and the PT growth between 12 and 24 months of corrected Gestational Age (GA). Methodology: An observational, longitudinal, prospective study carried out at the outpatient clinic of a university hospital, with a sample of 99 premature infants under 33 weeks of age discharged from the Neonatal Intensive Care Unit between June 1, 2021, and July 31, 2022. Excluding: PT infants of drug-using mothers, mothers using psychiatric drugs, adolescent mothers, PT who were adopted, who had special health needs or morbidities and malformations that interfere with growth, or who died during the follow-up period. The variables collected are related to the mother, the birth, the PT hospitalization period, and the outpatient follow-up up to 24 months of corrected GA. Maternal SE was assessed using the Preterm Parenting and Self-Efficacy Checklist instrument, answered by the mother during the outpatient visit between 12 and 24 months of corrected GA. Program R, XSLStat Cloud 2020, Statistical Package for the Social Sciences, and JASP were used for statistical analysis. Analyzes were carried out according to the purposes of each study, including the Chi-square test, Spearman or Pearson correlation, Welch tests, and Fisher Exact Test, among others. The statistical significance level was 5%. Results: Of the total sample, 56 (56.5%) were male, with an average GA of 30.2 weeks (± 2.0). Preterm parenting and Self-Efficacy Checklist instrument were reliable (Cronbach's Alpha 0.94) and had a mean total score of 6.14. There was an association between weight, height, head circumference, and time until reaching a full diet. There was an approximately 15-fold increase in the risk of growth failure in small-for gestational-age premature infants, for weight and head circumference. Clinical morbidities such as sepsis, bronchopulmonary dysplasia, metabolic bone disease, severe retinopathy of prematurity, and duration of parenteral nutrition use, presented upon admission by the PT, were associated with growth failure. Maternal SE was associated with variation in height. The magnitude of the effect of time until full enteral diet and weight was moderated by maternal self-efficacy. Each additional day of hospitalization resulted in a -0.02 decrease in the height Z score, with a moderating effect on maternal self-efficacy. Conclusions: When exploring the maternal and PT clinical factors that influence growth from birth to 24 months of corrected age, being born small for gestational age, intrauterine growth retardation, time to reach full enteral diet, time of use of parenteral nutrition, presence of morbidities such as necrotizing enterocolitis were associated with lower Z scores at two years. Self-efficacy moderates factors that interfere with growth and influence height and should be alert for monitoring the growth and health-disease process of children born prematurely.